2020
DOI: 10.1080/21645515.2020.1793713
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza vaccination during a pandemic

Abstract: In the Northern Hemisphere, the persistence or reemergence of coronavirus circulation into the 2020-2021 influenza season threatens to overwhelm health-care resources and systems and increase mortality and morbidity. Data from Australia show that stay-at-home policies have reduced both influenza and coronavirus cases early in the season, thus "flattening the curve." However, influenza vaccination is critical to ensure the reduction in co-infection. Several policies, such as vaccination strategies to accommodat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
7
0
6
Order By: Relevance
“…6 9 15-17 This is in addition to its potential indirect benefits, such as reducing the burden of additional respiratory illness among both individual patients and healthcare services. [18][19][20] This hypothesis has been supported by a limited number of observational studies, including five retrospective cohort studies 15 17 21-23 (three of which were limited by the use of aggregated data), demonstrating a negative association between influenza vaccination and COVID-19 outcomes including COVID-19 acquisition, severity and/ or mortality. One prospective study using individual-level data demonstrated a negative association between influenza vaccination and COVID-19 acquisition but did not report on subsequent COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…6 9 15-17 This is in addition to its potential indirect benefits, such as reducing the burden of additional respiratory illness among both individual patients and healthcare services. [18][19][20] This hypothesis has been supported by a limited number of observational studies, including five retrospective cohort studies 15 17 21-23 (three of which were limited by the use of aggregated data), demonstrating a negative association between influenza vaccination and COVID-19 outcomes including COVID-19 acquisition, severity and/ or mortality. One prospective study using individual-level data demonstrated a negative association between influenza vaccination and COVID-19 acquisition but did not report on subsequent COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 93%
“…38 Finally, influenza vaccination may also offer additional indirect protection against COVID-19 by reducing the burden of additional respiratory illness among both individual patients and healthcare services. [18][19][20] Strengths and limitations To our knowledge, this is the first study to examine influenza vaccination in relation to all-cause mortality and hospitalisation based on individual-patient data linked to demographic and clinical records in the UK. We applied robust analytic techniques to reduce the treatment indication bias that is inherent to observational studies.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…[20] In the context of COVID-19, the Australian government introduced measures to increase the uptake of influenza vaccination and emphasised the importance of pregnant women receiving the vaccine. [31][32] The time to immunity after influenza vaccination is approximately 2 weeks. [33] Influenza vaccination uptake in Australia increased from 3.5 million in 2018 to 7.3 million doses by May 2020 during lockdown, which may be attributed to effective public health messaging and increased health awareness during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa langkah yang dilakukan oleh pemerintah Australia untuk meningkatkan cakupan vaksinasi influenza di tengah pandemi COVID-19 yaitu memindahlan lokasi vaksinasi di luar ruangan (outdoor), memundurkan waktu vaksinasi menjadi di tengah puncak musim flu, meningkatkan cadangan serta distribusi vaksin influenza serta meningkatkan komunikasi dengan berbagai pemegang kebijakan termasuk media. 24 CDC dan WHO telah menyatakan bahwa vaksinasi influenza penting untuk mencegah terjadinya ko-infeksi influenza dengan COVID-19 yang dapat menyebabkan gejala lebih berat. 25 Pemberian vaksinasi influenza juga dapat mengurangi beban RS dalam merawat pasien influenza di tengah pandemi COVID-19.…”
Section: Vaksinasi Influenza DI Saat Pandemi Covid-19unclassified